Mediation of Job Burnout and Gender Moderation: The Influence of Work-Study Conflict on the Work-Life Balance of Working Students - Ariani, Finka; Fadli, Uus Mohammad Darul; Rosmawati, Ery (Research in Management of Technology and Business, 2026)
This study examines how Work-Study Conflict affects the quality of Work-Life Balance among working students. Using a quantitative approach, data were collected from 114 employed students in the Management Program, Class of 2022, at Buana Perjuangan University in Karawang. The data were analyzed with SEM-PLS in SmartPLS 4. Results indicate that Work-Study Conflict significantly and negatively influences Work-Life Balance. Job Burnout serves as a mediator in this relationship, exacerbating the challenges to life balance caused by the double pressure students face. Additionally, the moderation test showed that gender had no significant effect, indicating that both men and women experience similar levels of stress and challenges to their life balance. Overall, the study highlights that physical and emotional fatigue from balancing multiple responsibilities is a key obstacle to the well-being of working students. It recommends that students establish clearer boundaries to prevent work from interfering with academic responsibilities, and that companies and universities support more flexible schedules to help students maintain sustainable productivity.